RESISTANCE VALUES IN PALESTINIAN HIP-HOP MUSIC - Lutfiyah Alindah (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2012)
This research aims to describe popular culture of Palestine Hip-Hop and the values of songs. This research has purposes 1) to describe popular culture in Palestine Hip-Hop, and 2) to find resistance value in hip-hop songs. This research used popular culture approach of Adorno that analyzes three songs of DAM group, they are Who is the Terrorist?, Ghareeb fi Biladi, and Olive Trees. This research shows that 1) Hip-Hop music is the source of resistance Palestine through music media, 2) three of Hip-Hop songs not only give entertainment, but also have resistance values that have influences in national and international mass. Hip-Hop music is one of Palestine voice for Palestine in particular and Middle East in a wider context, so it describes the emergency condition of the regions. Key Words: Hip-Hop music, resistance value, and Palestine